President's Message - McKay, Marcy (Operating Room Nurses Association of Canada Journal, 2006)
It is hard to believe that summer is a mere breath away! After a busy spring, the summer season seems to be a time where we slow things down a little. In ORNAC’s world, however, we are as busy as ever.